Evaluation of the Involvement of Pharmacists in Diabetes Self-Care: A Review From the Economic Perspective - Jamshed, Shazia Q.; Siddiqui, Mohammand J.; Rana, Bareera; Bhagavathula, Akshaya S. (Frontiers in Public Health, 2018)
Abstract Objectives: To analyze the studies encompassing the involvement of pharmacists in diabetes self-care. Method: We reviewed studies conducted from 2005 to 2017 on the involvement of pharmacists in diabetes self-care. The keywords mainly used in this search are pharmacoeconomic analysis, diabetes self-care, pharmacist involvement, cost-effectiveness analysis, cost of utilization, cost of illness, cost of minimization and cost-benefit analysis. PubMed, Science Direct, Springer Link and Medline searched for the relevant studies. These databases searched for full text articles ranging from 2007 to 2017. We tried to limit the search with the inclusion of studies having any sort of pharmacoeconomically relevant component. Key findings: Cost of illness varied among the countries in managing diabetes mellitus, and the cost of managing diabetes complications were twice the cost of management of diabetes. Continuous involvement of the pharmacist in primary health care is a cost-effective strategy and pronounced to be essential for helping diabetes patient in controlling and managing their disease. Implementation of diabetes self-care by pharmacists such as lifestyle intervention rendered improved quality of life of patient without any increase in health care cost. Self-care management generates intensive blood glucose control and improved quality of life. Conclusions: Implementation of diabetic self-care intervention including intensive lifestyle intervention, education, self-monitoring of blood glucose and adherence towards medication-initiated reduction in the overall healthcare cost of diabetic patients compared to patients relying on only any one of the interventions. Impact of diabetes self-care intervention by pharmacist reported to significantly reduce the HbA1C levels of diabetic patients along with the reduction of yearly healthcare cost. This review showed that pharmacist involvement in diabetes self-care interventions prove to be cost-effective and can significantly affect the condition of the diabetic patients and reduces the risk of complications.